Dynamic Evolution Analysis of Stock Price Fluctuation and Its Control - Yuhua Xu; Zhongyi Ke; Chengrong Xie; Wuneng Zhou (Complexity)
This paper studies a simple dynamical system of stock price fluctuation time series based on the rule of stock market. When the stock price fluctuation system is disturbed by external excitations, the system exhibits obviously chaotic phenomena, and its basic dynamic properties are analyzed. At the same time, a new fixed-time convergence theorem is proposed for achieving fixed-time control of stock price fluctuation system. Finally, the effectiveness of the method is verified by numerical simulation.